Coorte de pacientes com leishmaniose visceral com ênfase em aspectos hematológicos - Cruz, Geydson Silveira da (2020)
Leishmaniasis are neglected tropical diseases caused by parasites of the genus Leishmania. According to the World Health Organization (WHO), there are an estimated almost 1,000,000 new cases annually in the world. Visceral leishmaniasis (VL) is the most serious clinical presentation, caused in Brazil by Leishmania infantum. The symptomatic infection leads to clinical manifestations such as fever, weight loss, hepatosplenomegaly, blood cytopenia, among others. Brazil is among the countries with the highest prevalence of VL, being the highest in the Americas. The Northeast region leads in the number of new cases and deaths from VL. Sergipe presented between 2010 and 2019, 687 diagnoses that caused 80 deaths. In this context, a cohort study was designed, based on the follow-up of patients with a confirmed diagnosis of VL in the period between December 2016 and June 2019. In the period, 70 cases were diagnosed, 68 analyzed. Most were male, the median age was 20 years old, 76.1% were under 40 years old. The median time to diagnosis was 30 days. Fever was reported in 91.2% of cases, followed by cutaneous-mucous pallor (83.8%) and evident weight loss (80.9%). Splenomegaly was noted in 75.0% of patients. Signs of severity were observed, such as febrile neutropenia (38.2%), jaundice (33.8%), and bleeding (14.7%). There was an inverse correlation between leukocyte count and time to diagnosis (rs: -0.31; p: 0.017). The risk score was less than 6 in 77.9% of diagnoses. The diagnostic test most performed was rK39, which was positive in 94.0% of the total of 63 samples collected. Bone marrow evaluation was performed in 45 patients, being positive on direct examination in 35 cases (74.5%), and bone marrow culture was positive in 28 (82.4%) collected cases. About hematological changes, anemia was the most diagnosed, present in 100% of cases, it was significantly more severe in the group at higher risk (p: 0.008). Twenty blood transfusions were performed. The relative risk of undergoing blood transfusion was 2.4 times greater in the high-risk group (p: 0.029; CI: 1.21-4.66). The most common treatment was liposomal amphotericin B (44.1%). Ten patients relapsed, 3 previously treated with liposomal amphotericin b, and 4 with antimonial. There was only one death in the study group, whose bone marrow showed signs of hemophagocytosis. The median follow-up of the group was 60 days, the survival analysis for treatment failure, relapse, and death events was estimated at 16.7% by the Kaplan-Meier methodology. There was no difference in the analysis of groups according to risk stratification. In conclusion, the present study points out that VL is present in all age groups and a large proportion of patients had a time for late diagnosis, severe patients are still frequently diagnosed, with significant changes in laboratory tests. The low lethality can be explained by the access to liposomal amphotericin B and the treatment carried out in a referral hospital. These data reinforce the need for investments in the VL assistance and diagnosis network, evaluation of the control and treatment program currently adopted and research on neglected diseases.